Pengembangan Media Berbasis Video Animasi Stop Motion Pada Materi Sistem Pencernaan Manusia - Aprilia Dhea Aztika; Nurul Fauziah (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2023)
Stop motion animated videos are animated videos created by manipulating video movement techniques from a combination of images that form as if the collection of images were like a moving video. This research aims to develop an animated video-based learning media on human digestive system material that is valid and practical. This research is included in Development research (R&D) using the Plomp development model. The data collection instruments used were validation sheets, interview sheets and validated practicality questionnaires. The sampling technique used is simple random sampling. Validation results by media experts show that the learning media developed has an average percentage of 96% (very valid). The validation results by material experts obtained an average percentage of 98.33% (very valid). The validation results by learning experts obtained an average percentage of 93.12% (very valid). The practicality results by students show that the media developed received an average percentage of 85.62% (very practical). The results of teacher practicality show that the media developed received an average percentage of 83.29 (very practical). The conclusion is that learning media based on stop motion animation videos on the human digestive system got a percentage of 95.81% in the very valid category and a percentage of 84.45% in the very practical category.